Roadmap for maternal behavior research in domestic dogs: lessons from decades of laboratory rodent work - Li, Ming (Frontiers in Veterinary Science, 2024)
Maternal behavior research in laboratory rats has revealed important behavioral and neurobiological mechanisms governing the onset, maintenance and decline of maternal behavior. However, the extent to which these mechanisms are evolutionarily conserved across species is less clear. This manuscript proposes that examining these mechanisms in dogs may be a viable approach to test their generality and help bridge the gap between rodent and human research, as domestic dogs show greater individual differences and exhibit more human-like maternal characteristics than rodents. These aspects represent advantages over rodent models, which in turn allow systems biological approaches not available in rodents. Additionally, domestic dogs share similar social environments with humans, suffer from the same mental disorders as humans, and can be treated with the same medications. This paper begins with a summary of key findings and theoretical developments from decades of rat maternal behavior research, followed by a literature review of the extant maternal behavior research on dogs and related methodology, highlighting the unique behavioral characteristics of dog maternal behavior and similarities and differences from rat maternal behavior. Finally, several knowledge gaps in dog maternal behavior research, as well as the future research in this area is discussed. It concludes that research on dog maternal behavior will not only advance our understanding of the universality of the neurobiological and behavioral mechanisms in maternal behavior, but also improve our understanding of risk factors associated with postpartum mental disorders.